Blockade of TrkB but not p75NTR activates a subpopulation of quiescent neural precursor cells and enhances neurogenesis in the adult mouse hippocampus. Issue 9 (14th January 2020) - Groves, Natalie; O'Keeffe, Imogen; Lee, Wendy; Toft, Alexandra; Blackmore, Daniel; Bandhavkar, Saurabh; Coulson, Elizabeth J.; Bartlett, Perry F.; Jhaveri, Dhanisha J.
Abstract: Brain‐derived neurotrophic factor (BDNF) signaling plays a major role in the regulation of hippocampal neurogenesis in the adult brain. While the majority of studies suggest that this is due to its effect on the survival and differentiation of newborn neurons, it remains unclear whether this signaling directly regulates neural precursor cell (NPC) activity and which of its two receptors, TrkB or the p75 neurotrophin receptor (p75 NTR ) mediates this effect. Here, we examined both the RNA and protein expression of these receptors and found that TrkB but not p75 NTR receptors are expressed by hippocampal NPCs in the adult mouse brain. Using a clonal neurosphere assay, we demonstrate that pharmacological blockade of TrkB receptors directly activates a distinct subpopulation of NPCs. Moreover, we show that administration of ANA‐12, a TrkB‐selective antagonist, in vivo either by systemic intraperitoneal injection or by direct infusion within the hippocampus leads to an increase in the production of new neurons. In contrast, we found that NPC‐specific knockout of p75 NTR had no effect on the proliferation of NPCs and did not alter neurogenesis in the adult hippocampus. Collectively, these results demonstrate a novel role of TrkB receptors in directly regulating the activity of a subset of hippocampal NPCs and suggest that the transient blockade of these receptors could be used to enhance adult hippocampal neurogenesis.